The Literary Ecology Forms and Implications of Guna Manusia Song Lyrics by Barasuara Band in Indonesian Language Learning - Guci, Aldo Ferdianda; Yani, Juli (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2023)
This research discusses the forms of literary ecology in the lyrics of Guna Manusia by the Band Barasuara and the implications for Indonesian language learning in Class X High School. The purpose in this research is to describe the ecological value of literature contained in the lyrics of Guna Manusia by Band Barasuara, in the form of the ecological values of pollution, natural disasters, residence or housing, and the earth, and their implications for learning Indonesian in class X High School. The approach used in this research is a qualitative one using the content analysis method. The data used in this research is finding out of quotations in the lyrics of the song Guna Manusia by Band Barasuara. The data collection techniques used documentation studies or literature studies. The lyrics of the song Guna Manusia by Band Barasuara are the main data source in this research. The results of the study found thirteen forms of literary ecological values contained in the lyrics of the song Guna Manusia by the band Barasuara. In the form of the ecological value of pollution, natural disasters, residence or housing, as well as the earth. The benefits of this research can be implicated and used as teaching material in learning Indonesian in class X, high school semester 2, with learning material for poetry musicalization.